Comparing the Representation of Crimes against Humanity in Kakay Fallah's Halabja Elegy and Tawfiq Amin Zayyad's Kafar Qasem Elegy - Esmaeil Barwasi (پژوهشنامه ادبیات کردی)
Kakay Fallah and Tawfiq Zayyad, prominent poets of the 20th century, lived under the oppressive regimes of Ba’ath and Zionist powers, bearing witness to atrocities against their Kurdish and Arab communities. Through their poetry, they reflect the suffering inflicted upon their people by totalitarian rulers, becoming voices for those deprived of basic rights in occupied Kurdistan and Palestine. This comparative study aims to analyze how crimes against humanity are portrayed in the poems of Kakay Fallah and Tawfiq Zayyad, exploring the themes and concepts intertwined with these atrocities. Employing a descriptive-analytical approach and a comparative sociological analysis, the research examines the prevalent motifs of bloodshed, darkness, death, civilian massacres, brutality, and barbarism in the poets' works. Kakay Fallah's verses evoke a deeper sense of anguish and sorrow compared to Tawfiq Zayyad's, as Fallah's elegy captures the magnitude of mass killings on a larger scale, surpassing the horrors depicted in Zayyad's portrayal of the Kafar Qasem massacre.